Conceptualization Of Gender -a Try Understand - nadjeh, MAKHLOUF (Journal of Social Sciences and Humanities, 2022)
Despite the controversy and ambiguity that surrounds it, however, the social gender - which has been identified with the term Gender - has become one of the concepts that necessitate the researcher, especially in the social sciences, to be familiar with it, due to its extreme importance in development, which is expected to lead to better living conditions for all and in all fields. And because it has become an analytical tool that helps to clarify the differences in the impact of the political, social and economic phenomenon on both women and men and its impact on each of them, and this paper contributes to dissecting the concept through the conceptual rooting of gender.